HUBUNGAN PENGETAHUAN IBU DENGAN KEMAMPUAN TOILET TRANING PADA ANAK USIA TODDLER DI RUANG RAWAT INAP E BLU RSUP Prof. Dr. R.D. KANDOU MANADO - Mokorimban, Hanny Ronald; Ismanto, Amatus Yudi; Hamel, Rivelino (e-NERS)
Abstract: Toilet training is an attempt to train children in urination and defecation. Ability to toilet training toddler age children need treatment as possible. Impacts affecting toilet training in children as the importance of the child,s nadines before initiating toilet training. The purpose of this study was to determine the relationship between mothers knowledge with the ability to toilet training toddler age children (1-3 years). This research was conducted by cross sectional method, the selection of samples with purposive sampling. Sample of 40 mothers withchildren aged 1-3 years. The research was carried out in December 2012 to Januari 2013. Data collection was done by filling koesioner made by researcher and completed by respondents. The results showed that there is a relationship between mothers knowledge with the ability to toilet training toddler age children. Conclusion there is a relationship with the mothers knowledge with the ability toilet training the toddler-age children in the inpatient department of E BLU Prof. dr. R.D. Kandou Manado. Advice for parents who have toddler 1-3 yearsin order to better prepare the children in the implementation of toilet training. Where is the knowledge, support and patience and agood example to help children in making toilet training independently. Keywords: Toilet Training, and mothers knowledge. Abstrak: Toilet Training adalah usaha untuk melatih anak dalam buang air kecil dan air besar. Kemampuan dalam pelaksanaan toilet training pada anak usia toddler perlu penanganan sedini mungkin. Dampak yang mempengaruhi toilet training pada anak adalah pengetahuan ibu dan pentingnya kesiapan anak sebelum memulai toilet training.Tujuan penelitian ini adalah untuk mengetahui hubungan pengetahuan ibu dengan kemampuan toilet training pada anak usia toddler (1-3 tahun). Penelitian ini dilaksanakan dengan metode cross sectional , pemilihan sampel dengan purposive sampling. Sampel 40 Ibu yang memiliki anak usia 1-3 tahun. Penelitian ini dilaksanakan pada bulan desember 2012 sampai januari 2013.Pengumpulan data dilakukan dengan pengisian koesioner yang dibuat oleh peneliti dan diisi oleh responden.Hasil penelitian menunjukkan bahwa ada hubungan antara pengetahuan ibu dengan kemampuan toilet training pada anak usia toddler. Kesimpulan Ada hubungan pengetahuan ibu dengan kemampuann toilet training pada anak usia toddler di ruang rawat inap E BLU RSUP Prof. dr. R.D. Kandou Manado. Saran bagi para orang tua yang mempunyai anak usia 1-3 tahun agar sedini mungkin mempersiapkan anak dalam pelaksanaan toilet training. Dimana pengetahuan, dukungan dan kesabaran serta contoh yang baik dapat membantu anak dalam melakukan toilet training secara mandiri. Kata Kunci: Toilet Training, dan pengetahuan ibu.